2022
DOI: 10.1002/hed.27031
|View full text |Cite
|
Sign up to set email alerts
|

Association between radiation dose to organs at risk and acute patient reported outcome during radiation treatment for head and neck cancers

Abstract: Background: Associations between patient-reported outcomes and dose to organs at risk (OARs) may promote management and guide future investigations. Methods: We retrospectively evaluated PROs and OAR dose in head and neck (H&N) cancer. Results: In 169 patients, we identified weak associations between: "Difficulty swallowing/chewing" and increased mean RT dose to the oral cavity, larynx, pharyngeal constrictor muscles (PCM) and contralateral parotid; "choking/ coughing" and larynx mean dose; "problems with mucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Animal studies have also characterized the molecular changes in irradiated vocal folds 28,29 . The severity of patient reported symptoms of dysphagia and aspiration due to these radiation changes has been correlated with radiation doses to the larynx and subglottic region 30–32 . Our study highlights that laryngeal dysfunction occurs even in patients who did not receive primary laryngeal irradiation.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Animal studies have also characterized the molecular changes in irradiated vocal folds 28,29 . The severity of patient reported symptoms of dysphagia and aspiration due to these radiation changes has been correlated with radiation doses to the larynx and subglottic region 30–32 . Our study highlights that laryngeal dysfunction occurs even in patients who did not receive primary laryngeal irradiation.…”
Section: Discussionmentioning
confidence: 61%
“…28,29 The severity of patient reported symptoms of dysphagia and aspiration due to these radiation changes has been correlated with radiation doses to the larynx and subglottic region. [30][31][32] Our study highlights that laryngeal dysfunction occurs even in patients who did not receive primary laryngeal irradiation. In addition to radiation to the larynx, increased radiation doses to the oral cavity, pharyngeal constrictor muscles, and contralateral parotid and submandibular glands were similarly associated with difficulties with swallowing, chewing, voice and speech production, coughing, chocking, mucus in mouth, and dry mouth.…”
Section: Discussionmentioning
confidence: 66%
“…These studies considered the glottic and supraglottic larynx components either separately 4 , 6 , 11 , 16 or together as a single structure. 7 , 8 , 12 , 17 , 20 The definition of the supraglottic larynx was variable and not always given in many of these studies, making it challenging to generalize about their relevance to the epiglottis. Dornfeld et al 14 did consider the epiglottis, but only as a point dose in the vicinity and not from a contoured structure's DVH.…”
Section: Discussionmentioning
confidence: 99%
“… 1 The larynx is a key organ in the swallowing process, as it contains the epiglottis, a cartilaginous mucosal flap that folds over the opening to the glottis and airway during swallowing to prevent food from entering the trachea. Although it is generally recognized that a dose relationship exists between the larynx and swallowing difficulties, 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 there is uncertainty in knowing what region of the larynx is most sensitive to swallowing dysfunction after irradiation. This uncertainty has led to variations in what is anatomically contained in a larynx structure delineated for H&N treatment planning.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we observed low correlations between selected PROs with the radiation doses received by their associated OARs across all patients included in this substudy, a finding which has been observed in other series. 37 This suggests that patientreported assessment of symptom burden is more complex than simply the dosimetry calculated from a single pretreatment simulation scan.…”
Section: Discussionmentioning
confidence: 99%